Optimum technique for maximising forward somersault rotation in trampolining - Burke, D.; Yeadon, F.; Hiley, M. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to investigate the optimal technique to produce somersault rotation in forwards rotating somersaulting skills. A 7-segment planar, torque-driven simulation model of a trampolinist was developed. The trampoline was represented by horizontal and vertical force-displacement relationships. The model was evaluated using recorded performances of three forward somersaulting skills. Optimised takeoff technique produced an increase of 9% in rotation potential using a more open shoulder angle and a greater initial horizontal velocity.